MANAGEMENT OF BUDDHIST RELIGIOUS EDUCATION; CHALLENGES IN MAINTAINING THE EXISTENCE OF DHAMMASEKHA SCHOOL. - Widia Darma; Yunika Triana (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
This study aims to determine the strategy in maintaining the existence of the Nava Dhammasekha Virya Guna school in Jepara Regency. This study uses a qualitative approach with a case study at Nava Dhammasekha Virya Guna School, Jepara Regency. Informants consist of the Head of the Foundation, the principal, one teacher, one education staff, one community leader and one representative of the student's parents. Data collection uses observation, interviews, and document studies. Data validity is in the form of credibility, dependability, transferability, and confirmability. Data analysis uses an interactive model. The challenges in maintaining the existence of the Nava Dhammasekha Virya Guna school can be seen from three current challenges such as; 1) The brand and image of the Dhammasekha school which is not yet strong in the community, 2) Limited segmentation and market, 3) Support from the community and stakeholders which is not yet optimal. This research will be useful for the Government, especially Direktorat Jenderal Bimbingan Masyarakat Buddha Kementerian Agama, Nava Dhammasekha School Organizers and Education Observers.